A Pilot Study for Forgiveness Intervention in Adolescents With High Trait Anger: Enhancing Empathy and Harmony - Tao, Linjin; Ji, Mingxia; Zhu, Tingting; Fu, Hong; Sun, Ruoying (Frontiers in Psychology, 2020)
Forgiveness interventions benefit victims’ mental health, reduce levels of anger, and promote forgiveness. However, forgiveness interventions are rarely used to improve the offender’s anger and mental health, especially in specific situations such as juvenile correctional facilities. The offender is often also a victim, and reducing the offender's excessive anger may prevent or decrease the likelihood of future interpersonal violence. This study examined the effects of forgiveness interventions on anger, forgiveness, empathy, and harmony of juvenile delinquents with high levels of trait anger. Eighteen adolescents with trait anger in a juvenile correctional facility volunteered to participate in group counseling. A pretest-posttest method of quasi-experimental design was used, with 8 participants in the intervention group and 10 in the control group; the intervention group received forgiveness group counseling, and the control group did not. The results revealed that the intervention group had significantly higher scores for forgiveness, empathy, and harmony than the control group, though no significant differences in the scores of state and trait anger were found. However, the effect size on the total score of state anger and the two dimensions of trait anger were moderate. The forgiveness intervention had significantly improved the levels of forgiveness towards specific perpetrators of childhood victimization for the juvenile delinquents with high levels of trait anger, raising their levels of empathy and harmony; there was no significant increase in trait anger. The findings indicated that forgiveness intervention provides an effective way to improve the positive mental strength of adolescents with high levels of trait anger.